Adaptations in Protein Expression and Regulated Activity of Pyruvate Dehydrogenase Multienzyme Complex in Human Systolic Heart Failure. (7th February 2019) - Sheeran, Freya L.; Angerosa, Julie; Liaw, Norman Y.; Cheung, Michael M.; Pepe, Salvatore
Abstract : Pyruvate dehydrogenase (PDH) complex, a multienzyme complex at the nexus of glycolytic and Krebs cycles, provides acetyl-CoA to the Krebs cycle and NADH to complex I thus supporting a critical role in mitochondrial energy production and cellular survival. PDH activity is regulated by pyruvate dehydrogenase phosphatases (PDP1, PDP2), pyruvate dehydrogenase kinases (PDK 1-4), and mitochondrial pyruvate carriers (MPC1, MPC2). As NADH-dependent oxidative phosphorylation is diminished in systolic heart failure, we tested whether the left ventricular myocardium (LV) from end-stage systolic adult heart failure patients (n = 26 ) exhibits altered expression of PDH complex subunits, PDK, MPC, PDP, and PDH complex activity, compared to LV from nonfailing donor hearts (n = 21 ). Compared to nonfailing LV, PDH activity and relative expression levels of E2, E3bp, E1 α, and E1 β subunits were greater in LV failure. PDK4, MPC1, and MPC2 expressions were decreased in failing LV, whereas PDP1, PDP2, PDK1, and PDK2 expressions did not differ between nonfailing and failing LV. In order to examine PDK4 further, donor human LV cardiomyocytes were induced in culture to hypertrophy with 0.1 μ M angiotensin II and treated with PDK inhibitors (0.2 mM dichloroacetate, or 5 mM pyruvate) or activators (0.6 mM NADH plus 50 μ M acetyl CoA). In isolated hypertrophic cardiomyocytes in vitro, PDK activators and inhibitors increased and decreased PDK4, respectively. In conclusion, in end-stage failing hearts, greater expression of PDH proteins and decreased expression of PDK4, MPC1, and MPC2 were evident with higher rates of PDH activity. These adaptations support sustained capacity for PDH to facilitate glucose metabolism in the face of other failing bioenergetic pathways.